Vote of judges as an element constituting iudicium part. 2 - vote as an act of judges' power and its psychological conditioning - POKORSKI, KRZYSZTOF (Prawo Kanoniczne, 2019)
The canonical matrimonial process, which is a series, defined by the law and necessary to perform the activities of the judge, whose task is to recognize and resolve the case. Therefore, a church judge is not only the executor of a legal norm, but also interprets it in the perspective of the presented facts and events. Judging the case is a process that combines the procedural, intellectual, moral and psychological aspects of the judge. The church judge, for his decision, not only possesses knowledge and experience, but also personal qualities and individual mental characteristics.